ANALISIS PENAMBAHAN LIMBAH KERTAS TERHADAP KUAT TEKAN BETON RINGAN - HADI, H. SURYA (Universitas Mahasaraswati Mataram, 2018)
West Nusa Tenggara (NTB) is included in the area of the earthquake path, therefore the use of lightweight concrete materials is very useful in infrastructure development in earthquake prone areas. There are several advantages in using lightweight concrete such as; smaller density of concrete, thus reducing the weight of structural elements resulting in diminishing dimensional requirements. The light weight of this type affects the dead load of smaller structures as well, also can reduce the size of the required foundation volume. The purpose of this study was to investigate the effect of adding waste paper on lightweight concrete with aggregate of pumice stone.In this study used 9 (nine) pieces of cylindrical test specimens with a diameter of 150 mm and height 300 mm. where 3 test specimens use 1Pc: 2Ps: 3Ba ratio with 0% paper additives, with an average compressive strength of 17.342 MPa, 3 test specimens using 1Pc: 2Ps: 3Ba ratio with 10% paper addition, average of 20,324 Mpa, and 3 test specimens using 1Pc: 2Ps: 3Ba ratio with 20% paper addition, with an average compressive strength of 18,874 Mpa. The addition of waste paper by 10% shows the highest compressive strength of 20,324 Mpa.